Program Literasi Media Televisi untuk Penguatan Minat Baca Siswa - Alfandi, M. (LP2M of Institute for Research and Community Services - UIN Walisongo, 2016)
Lack of attention and guidance from parents to children, resulting in the child will be negatively affected in the use media.Minat kids to reading material that is very important for children of school age actually outweighed by the interests of children to television. Media literacy programs required to address issues Government Elementary School students (MI) Al-Hikmah Ngadirejo Hamlet Village Resources Simo Boyolali District of which are susceptible to the negative influence of television media. Also the students are still low interest in reading. Results of media literacy is the strengthening of the students' interest in reading MI Alhikmah Source Simo Boyolali and increased knowledge and understanding of students and parents about the negative and positive impacts of the television media.